EFEKTIVITAS BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) SEBAGAI PERLINDUNGAN SOSIAL DAN PEMULIHAN EKONOMI DALAM MENDUKUNG PEMBANGUNAN DESA DI DESA SUMORAME KECAMATAN CANDI KABUPATEN SIDOARJO - Erlidha Catur Difayanti; Isna Fitria Agustina (Journal Publicuho, 2025)
This study aims to analyse the effectiveness of the distribution of Village Fund Direct Cash Assistance (BLT-DD) in Sumorame Village, Candi District, Sidoarjo Regency. The research focuses on five indicators of program effectiveness, namely target accuracy, timeliness, amount accuracy, goal achievement, and beneficiary satisfaction. The study employed a qualitative descriptive method with data collected through interviews, observation, and documentation. The findings reveal that the distribution of BLT-DD in Sumorame Village is generally considered moderately effective. Target accuracy was relatively achieved, although some poor households were excluded due to quota limitations. The distribution was carried out according to the schedule but faced delays at the higher-level disbursement process. The amount of assistance complied with regulations, yet it was perceived as insufficient to meet basic household needs. The program contributed to maintaining household purchasing power and reducing potential social tensions, although its impact on village-wide economic recovery remained limited. Beneficiary satisfaction varied, with most recipients feeling helped, while others considered the support insignificant. Therefore, the implementation of BLT-DD in Sumorame Village requires improvement through better data management, enhanced transparency, and integration with community empowerment programs.